Percikan Filosofis Al-Wujud Mulla Sadra terhadap Tradisi Filsafat Islam - sholeh, muh ibnu sholeh; Munif, M; Sokip; Syafi’i, Asrop (UPT Publikasi Ilmiah, 2024)
This research examines the concept of al-Wujud (Being) in Mulla Sadra’s thought, which significantly influences Islamic philosophy. Mulla Sadra, a prominent philosopher in the Islamic tradition, developed this concept by emphasizing the philosophical view that everything in existence is merely a manifestation of a Single Being, which is God. This study employs the library research method by analyzing Mulla Sadra’s major works and comparing them with the views of other Islamic philosophers, such as Ibn Arabi and Suhrawardi. The findings indicate that Mulla Sadra’s Philosophy of Being aligns closely with the concept of Wahdat al-Wujud (Unity of Being), deeply intertwined with the systematic framework of Islamic philosophy, encompassing ontological, cosmological, theological, and ethical aspects. One of Mulla Sadra’s major contributions is his theory of substantial motion (al-harakat al-jauhariyyah), which posits that every entity in the universe undergoes substantial change towards the perfection of existence. This theory supports the idea that all beings are continually moving towards unification with the Divine Being. This concept enriches the metaphysical understanding in Islamic philosophy, where reality is viewed as a connected spectrum of existence, and human ethics are directed towards spiritual perfection, ultimately leading to closeness with God. Furthermore, the research touches on a comparative analysis of Mulla Sadra’s Philosophy of Being with the thoughts of Ibn Arabi and Suhrawardi, offering relatively new insights into the integration of spirituality and rationality in the evolution and development of Islamic philosophy.